What role do normal force and frequency play in the tribocorrosion behaviour of Ti-6Al-4 V alloy?. (August 2022) - Feyzi, Mohsen; Fallahnezhad, Khosro; Taylor, Mark; Hashemi, Reza
Abstract: This paper studies the tribocorrosion behaviour of Ti-6Al-4 V in phosphate buffered saline under reciprocating frequencies of 1, 5, 10, 15, 20, and 25 Hz at different normal forces of 3.5, 6, 10.8, and 17.5 N using a customised ball-on-disk test set-up. The tribocorroded scars were then post-assessed by scanning electron microscopy and energy dispersive x-ray spectroscopy, atomic force microscopy, profilometry, and confocal microscopy. The results demonstrated a unique pattern for the total volume loss versus frequency such that the loss was maximum at 5 Hz with a subsequent reduction from 5 to 15 Hz, and a final stabilisation beyond 15 Hz. Compared to the total and chemical losses, mechanical volume loss showed more significant variations with frequency. The results indicated complex interactions between the normal force and frequency in relation to the total material loss from the alloy. These findings challenge the general understanding of an increase in the total loss with increasing frequency. Highlights: Tribocorrosion of Ti-6Al-4 V was studied under various normal forces and frequencies. Variations in total material loss with frequency with a maximum occurring at 5 Hz. Mechanical part of total material loss was more sensitive to changes in frequency. Complex interactions between normal force and frequency determined the total loss.